1995
DOI: 10.1111/j.1469-8986.1995.tb01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of baroreflex control from beat‐to‐beat blood pressure and heart rate changes: A validation study

Abstract: In this study, we tested the validity of a new method designed to estimate baroreflex control of heart rate from spontaneous changes in systolic pressure and pulse interval. This method was compared with a conventional method of assessing baroreflex control through measuring reflex adjustments in pulse interval associated with pharmacological manipulations of blood pressure. The estimates of baroreflex control derived from the two methods were significantly correlated; however, only the estimate derived using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 9 publications
3
30
0
Order By: Relevance
“…The baroreflex nature of sequences has been demonstrated in a previous study, which revealed a dramatic reduction in both up and down sequences after sinoaortic denervation in unanesthetized cats. 26 In accordance with the results of previous studies, 10,27,28 we did not find any difference between the up and down slopes, and the analysis made without separating them made it possible to obtain information on BRS in the whole study population. A significant positive correlation between the sequence method and phenylephrine has been found in healthy subjects 12 and in hypertensive patients.…”
Section: Sequence Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…The baroreflex nature of sequences has been demonstrated in a previous study, which revealed a dramatic reduction in both up and down sequences after sinoaortic denervation in unanesthetized cats. 26 In accordance with the results of previous studies, 10,27,28 we did not find any difference between the up and down slopes, and the analysis made without separating them made it possible to obtain information on BRS in the whole study population. A significant positive correlation between the sequence method and phenylephrine has been found in healthy subjects 12 and in hypertensive patients.…”
Section: Sequence Analysissupporting
confidence: 91%
“…A significant positive correlation between the sequence method and phenylephrine has been found in healthy subjects 12 and in hypertensive patients. 13 However, Watkins et al 27 have also shown that there are differences between the two methods in subjects with irradiated baroafferents, in whom BRS was found to be reduced only when evaluated by use of the vasoactive drug, despite the good correlation found between the two measurements.…”
Section: Sequence Analysismentioning
confidence: 99%
“…It is a physiological technique for the assessment of baroreflex sensitivity at rest that does not require the use of vasoactive drugs with direct effects on afferent, central, or efferent components of the reflex arc [7, 12, 13]. In our study, baroreflex sensitivity obtained by the sequence method at rest significantly correlated with that obtained by the Valsalva maneuver in healthy volunteers and patients with Parkinson’s disease.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, baroreceptor sensitivity may be evaluated on the basis of fluctuations in blood pressure and associated changes in R–R interval. Several authors have referred to this technique as the sequence method [7, 13, 14]. However, baroreflex sensitivities cannot be measured by the sequence method in some patients with autonomic dysfunction at rest because fluctuations in blood pressure are too small and lack significant correlation with changes in R–R intervals [15].…”
Section: Introductionmentioning
confidence: 99%
“…Because of these issues, a new technique has recently been employed in which arterial baroreflex function is assessed by correlating beat-to-beat fluctuations in arterial pressure with HR, i.e., evaluation of spontaneous baroreflex function (1,2,5,18). A variation of this spontaneous method has also been described (see Ref.…”
mentioning
confidence: 99%